Cultural Transformation In the Short Story “Nihayatus Syaykh” By Ali Thanthawi: A Postcolonial Analysis - Rasyidah Almardhiyah; Rasyad Rasyad; Anshar Zulhelmi Zulhelmi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study investigates the process of cultural transformation depicted in Ali Thanthawi’s short story “Nihayatus Syaikh” through the lens of Edward Said’s postcolonial framework, particularly the concept of Orientalism. The central problem addressed in this research is the tension between traditional Arab cultural values and the forces of colonial modernization, which reshaped social structures, educational systems, and identity formation in early twentieth-century Arab society. To examine this issue, the study employs a qualitative descriptive method, focusing on textual interpretation and thematic analysis. The objective is to reveal how the narrative reflects shifts in cultural norms and to understand the protagonist’s—an elderly traditional teacher—struggle in responding to these changes. The analysis shows that cultural transformation in the story occurs at multiple levels. Administratively, the requirement for formal diplomas symbolizes the institutionalization of Western educational standards. Morally and socially, the younger generation’s adoption of modern, individualistic, and Western-oriented lifestyles represents a departure from earlier values such as simplicity, humility, and religiosity. The short story further critiques the declining respect for local scholarly authority and the erosion of intellectual dignity amid rapid modernization. The findings demonstrate that colonial influence is not limited to political or structural dimensions but also permeates cultural consciousness, shaping how individuals perceive their own identity. The contribution of this study lies in positioning “Nihayatus Syaikh” as a cultural document that reveals complex dynamics of resistance, adaptation, and loss within a postcolonial context. This research highlights the need to preserve cultural awareness and critical reflection when navigating modernization pressures.